Strategi Usaha Kecil Menghadapi Digitalisasi Pemasaran - Sudirman, Eddy (Universitas muhammadiyah palembang, 2020)
Small and medium businesses (SMEs) face the biggest challenges since the rise of online system sales. Shifting mindset and patterns of public service to the needs of an item needs to make SMEs who do not understand the development of information technology become worse and close their businesses. However, actually the phenomenon that occurs in society is only the marketing pattern but production remains a necessary factor. This type of descriptive qualitative research with the aim of getting an in-depth overview of the phenomena that occur then linked with journals to find solutions to these problems. The methodology used in research journals. The novelty model concept is found in this study, the dimensions of the model concept are explained in detail.